2010
DOI: 10.1111/j.1944-9720.2010.01094.x
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of Immersion and Instruction on Second Language Pronunciation

Abstract: This preliminary study investigates the acquisition of second language phonology with respect to two variables: immersion in a target language community, and explicit instruction in the form of a phonetics/pronunciation class. Specifically, the research examines the second language acquisition (SLA) of specific properties of the Spanish phonology system as achieved by native speakers of English participating in a summer program in Mexico, some of whom had previously taken a Spanish phonetics course. Results su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 36 publications
(57 reference statements)
5
54
1
1
Order By: Relevance
“…Taken together, these reports suggest that immersion catalyzes learners' acquisition of Spanish spirantization. However, repeated-measures designs including a pre-and posttest have shown that learners' production changes little after studying abroad (Díaz-Campos, 2004;Lord, 2010;Nagle, Morales-Front, Moorman, & Sanz, 2016). For example, Díaz-Campos (2004) found that study abroad participants were no more likely to produce [ð] and [ɣ] after studying in Spain for ten weeks than they were beforehand.…”
Section: Second Language Acquisition Of Spanish Approximantsmentioning
confidence: 99%
“…Taken together, these reports suggest that immersion catalyzes learners' acquisition of Spanish spirantization. However, repeated-measures designs including a pre-and posttest have shown that learners' production changes little after studying abroad (Díaz-Campos, 2004;Lord, 2010;Nagle, Morales-Front, Moorman, & Sanz, 2016). For example, Díaz-Campos (2004) found that study abroad participants were no more likely to produce [ð] and [ɣ] after studying in Spain for ten weeks than they were beforehand.…”
Section: Second Language Acquisition Of Spanish Approximantsmentioning
confidence: 99%
“…No effect of instruction was found on the degree of perceived foreign accent in the speech of the L2 learners. In Lord (2010), English learners of Spanish who had taken a Spanish phonetics course were found to be more accurate than those who did not in producing three Spanish allophones. However, it is difficult to attribute this advantage to pronunciation instruction, as no data prior to instruction was available.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A number of these studies have focused on the effect of teaching segments or individual sounds on the accuracy of L2 pronunciation (Derwing and Rossiter, 2003;Lord, 2005;Saito, 2007;Lord, 2010;Saito, 2011;Saito and Lyster, 2012;Kissling, 2013;Saito, 2013;Sturm, 2013;Derwing, Munro, Foote, Waugh and Fleming, 2014;Kennedy, Blanchet and Trofimovich, 2014). Derwing and Rossiter (2003) showed that the teaching of segments or individual sounds to L2 English learners, who were of different L1 backgrounds, was not effective in reducing the degree of perceived foreign accent in their speech.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, research in the field of speech perception indicates that listeners can detect foreign accent in their native language in segments as short as 30 ms (Flege, 1984). Studies with regard to L2 phonology have also noted a general lack of discussion of L2 sounds in the classroom (Lord, 2010;Elliot, 1995b). If foreign accent is so noticeable, why is it not discussed at earlier levels of language instruction?…”
Section: Introductionmentioning
confidence: 99%
“…theory, discussion of articulatory phonetics) aids in the target-like production of L2 sounds (Lord, 2010;De Wilde, 2009;Huthaily, 2008), as opposed to the debate in morphosyntax. This may be due to the fact that L2 phonology has a neuromuscular basis and thus is more constrained by the critical period than other language skills (Elliot, 2003;Scovel, 1988).…”
mentioning
confidence: 99%